Primary B-Cell lymphoma of the mandible: a potentially difficult diagnosis. (2nd July 2019) - King, Hudson; Rogers, Simon
Abstract : There are many causes of a persistent unilateral numbness of the lower lip. A case report of a 34-year-old normally fit and well male, whose symptoms of numbness of the mandibular division of the right trigeminal nerve represented the rare diagnosis of a primary B-cell lymphoma of the mandible, is presented here. The patient's presentation and management, reasons for the difficulty in ascertaining a definitive diagnosis, as well as invaluable points to be reflected on from this case, are discussed. CPD/Clinical Relevance: Numbness should be treated with a high degree of suspicion, with urgent imaging, biopsy and specialist histopathology staining being carried out to exclude malignancy.